Investment Trends in Hyderabad, Pakistan - Parmar, Vishnu; Jalbani , Amanat Ali (JISR management and social sciences & economics, 2005)
The investment trend in Pakistan fluctuated from province to province, urban to rural, and urban to urban. Small cities of yesteryears have emerged as big cities like Gujranwala, Gujrat, Sialkot, Multan, Rawalpindi, and Faisalabad, while some major centers of trade and business in the past like Thatta, Bhanbhore, Shikarpur, Khairpur, and Hyderabad have ruined. Hyderabad, the second largest city of the province and sixth in the country had flourished in Large Scale Manufacturing until 1980s. Today, the city is loosing its glorious past, the existing units are converting into sick, and the new investment is stagnant. This research paper focuses on the investment trends in Hyderabad, and identifies some causes and consequences of the trend.